Konsep Masjid Perspektif Hadratussyaikh KH. M. Hasyim Asy’ari - M. Fawaz Al-Badawi; Hanifudin (CV. Creative Tugu Pena, 2024)
This journal aims to explore and analyze his concept of the mosque, encompassing its societal roles, etiquettes within the mosque, worship activities, as well as recommendations and prohibitions related to the mosque. This study is a library-based research utilizing interpretative and historical approaches to analyze the concept of the mosque according to Hadratussyaikh KH. M. Hasyim Asy’ari. The interpretative approach evaluates behavior in detail by observing the context and social meanings, while the historical approach investigates historical events and reconstructs them into a documented narrative. According to Hadratussyaikh KH. M. Hasyim Asy’ari, the construction of mosques in every city and village is considered a collective obligation (fardhu kifayah), essential for promoting Islamic symbols. The construction of mosques, whether large or small, must be carried out sincerely for the sake of Allah. Regarding mosque decoration, Hadratussyaikh advises simplicity to avoid disrupting the congregation's concentration. Excessive decoration is deemed makruh (discouraged) as it may divert attention from the primary purpose of worship. In emergency situations, such as significant population growth or long distances between homes and the mosque, building two mosques in one village is permissible to meet the community’s worship needs. However, in general, this practice is not recommended to avoid division among congregants